Calculating of Month and Day of Birth Ahead of The Wedding Day in The Javanese Culture: Perspective of Maqashid Al-Syari’ah - Mas’ud; Mas'ud (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2024)
Background. Counting the month and day of birth is ritual; respect for traditions and beliefs that have existed for a long time in society; considered as one way to ensure that the couple starts their new life well and receives blessings from God. Aim. Examines the role of Javanese culture in calculating the month and day of birth in relation to the upcoming wedding, as well as its relevance from the perspective of maqashid al-shari’ah. Method. Qualitative approach involving in-depth interviews and participatory observation. Thematic analysis was employed to identify key themes of data and to connect with the theory of maqashid al-shari’ah. Results. The practice carries values aligned with maqashid al-shari’ah, such as the protection of offspring and the formation of harmonious family relationship; provides spiritual and social reinforcement for the Javanese community; fostering mutual respect and strengthening the bonds between individuals and their traditions and beliefs.